DYNAMIC ANALYSIS OF THE COVID-19 MODEL WITH ISOLATION FACTORS - Dewi, Atika Ratna; Ananda, Ridho; Rifanti, Utti Marina (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Covid-19 is a type of infectious disease caused by SARS Cov-2. This virus has spread throughout the world to cause a pandemic. This study aimed to model and analyze the spread of Covid-19 with the isolation factor. The spread of Covid-19 can be made into an epidemic model by taking into account the population of susceptible humans (S), infected humans (I), isolated humans (L), and recovered humans (R). The method used in this research was to derive a non-linear system of differential equations model, complete the model qualitatively, find the primary reproduction ratio ( , see the model’s behavior by analyzing the dynamics of the equilibrium point and make model simulations. This model has a disease-free equilibrium point that is asymptotically stable, while at the equilibrium point, the endemic is unstable. The results of the model simulation and analysis of the value indicate that the chance of successful Covid-19 spread and the isolation factor is a significant controlled parameter in reducing the value.